Perception and adoption of digital technology in students’ data management: A case study of tasmik program - Husni, M.; Jaya, M. Izham; Eh Phon, Danakorn Nincarean; Hisham, Syifak Izhar; Ab Razak, Mohd Faizal (Philstat.org.ph, 2022)
With the emergence of digital technology, inefficiencies of the manual process in managing students’ data can be reduced, bringing more possibilities to the teachers to strike a balance between their teaching approach, students’ progress and the expected outcomes. Therefore, this paper presented a quantitative study aimed to analyse the readiness level among teachers in the Tasmik program towards the adoption of digital technology for managing student’s data. Additionally, this paper also aimed to examine the correlation between the level of readiness to adopt digital technology among Islamic education teachers and the effectiveness of the proposed e-Tasmik digital tool. This study employed a quantitative research design using questionnaire-based survey. The respondents representing Islamic education teachers at four national primary schools in Pahang, Malaysia denote urban, suburban, and rural areas. Data is analysed using SPSS and Spearman Rho correlation test. Further analysis revealed that the respondents hold negative perception on the usefulness of the existing manual method and believe that they are ready to adopt digital technology for data recording, analysis and reporting. There is a weak correlation between the teachers’ readiness level and e-Tasmik effectiveness which show that the readiness level among Islamic education teachers does not determine the effectiveness of e-Tasmik in terms of its Perceived Ease of Use (PEoU), Perceived Usefulness (PU) and User Acceptance (UA). This paper helps the stakeholders in Malaysia Islamic education to tailor teachers’ needs with available digital technologies such that it will help to improve effective learning and teachers’ productivity.